Intelligenza umana e artificiale: un’alleanza possibile? - Nunnari, Patrizia (B@belonline, 2024)
Human intelligence can undoubtedly beat the algorithms of artificial intelligence, not for the prowess in the speed of calculation and for the extension of its memory, an ability with which human intelligence is often defined in a truly reductive way, but for the complexity it has always enjoyed in its deeply embodied, intuitive, conscious, heuristic being. It is not so much the comparison as the relationship that can be built between the two, avoiding traditional biases and bringing out both the main differences and the possible “alliances,” with a view to a reflexivity that avoids catastrophic postures or easy enthusiasms, choosing instead the epistemological will to integrate and compensate, distinguish and join, without ever separating.